Portable biosensors and point-of-care systems - Kintzios, Spyridon E. (The Institution of Engineering and Technology, 2017)
This book describes the principles, design and applications of a new generation of analytical and diagnostic biomedical devices, characterized by their very small size, ease of use, multi-analytical capabilities and speed to provide handheld and mobile point-of-care (POC) diagnostics.
Keywords: Biosensors.; Detectors.; Point-of-care testing.; elektronické knihy; electronic books